PERBAIKAN CITRA MENGGUNAKAN HISTOGRAM EQUALIZATION PADA DETEKSI TEPI BATIK - retno wahyusari (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2019)
ABSTRACTIndonesia has 17 diverse cultures that have been recognized by UNESCO, one of which is batik.There is recognition from UNESCO that Indonesian cultural heritage of batik may not berecognized by other countries. Batik as a cultural heritage has its own uniqueness, to maintain theuniqueness of batik, it is necessary to document batik motifs. Batik motifs can be documented bychanging batik motifs into images or images. One way to change batik motifs into images is by using optical devices such as cameras,scanners, and so on. The authenticity of batik motifs from the documentation needs to be done bydetecting the edge of the batik so that the batik motif can be maintained properly. One methodused is to use the canny method in Matlab 2013, but edge detection with canny has weaknesses inimages that have uneven gray values, so to level up the grayishness of batik it is necessary toimprove the image using the histogram equalization method. Detection of batik edges with image improvement using histogram equalization methodand canny method can improve the detection results with the number of test data 13 with a totalof batik images that can be repaired 10 batik images and 3 batik images have not been able to berepaired. The best MSE value is 0.229538 and PSNR is 54.5563. Poor value with MSE 0.676356and PSNR 49,863.